2016
DOI: 10.1016/j.ajpath.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

SAG/Rbx2-Dependent Neddylation Regulates T-Cell Responses

Abstract: Neddylation is a crucial post-translational modification that depends on the E3 cullin ring ligase (CRL). The E2-adapter component of the CRL, sensitive to apoptosis gene (SAG), is critical for the function of CRL-mediated ubiquitination; thus, the deletion of SAG regulates neddylation. We examined the role of SAG-dependent neddylation in T-cellemediated immunity using multiple approaches: a novel T-celle specific, SAG genetic knockout (KO) and chemical inhibition with small-molecule MLN4924. The KO animals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…IFN-γ, IL-2 and IL-4), which is required for efficient Th1 and Th2 differentiation [70], demonstrating a potent positive function of neddylation pathway in T-cell activation [69, 71]. Consistently, deletion of RBX2 significantly decreased T-cell activation and T-effector cytokine release upon in vitro allogeneic stimulation [72].…”
Section: Introductionmentioning
confidence: 99%
“…IFN-γ, IL-2 and IL-4), which is required for efficient Th1 and Th2 differentiation [70], demonstrating a potent positive function of neddylation pathway in T-cell activation [69, 71]. Consistently, deletion of RBX2 significantly decreased T-cell activation and T-effector cytokine release upon in vitro allogeneic stimulation [72].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, previous studies (both ours and others) have shown that SAG and SAG-dependent neddylation play a critical role in regulation of the inflammatory response involving several immune cells, including macrophages (9), dendritic cells (16), and T-cells (30), and interestingly, in human hepatocellular carcinoma cells as well (31, 32). Specifically, inactivation of Sag by siRNA-mediated knockdown or chemical inhibition of neddylation with MLN4924, a potent small molecular inhibitor of NEDD8 activating enzyme E1 NAE that effectively blocks cullin neddylation to inhibit CRL activation (33), impaired inflammatory response.…”
Section: Discussionmentioning
confidence: 59%
“…Besides, further research reveals that the sensitive to apoptosis gene (SAG), a neddylation E3 ligase, collaborates with UPS to promote survival of infectious macrophages via degrading proapoptotic Bax and sterile α and HEAT/armadillo-motif-containing protein (SARM) (112). SAG also affects cytokine secretion of macrophages (113). Similar to innate immune cells, SAG-deficient T cells also show decreased proliferation, reduced production of cytokines, and diminished release of the T-cell lineage.…”
Section: Neddylation and Hccmentioning
confidence: 99%
“…Similar to innate immune cells, SAG-deficient T cells also show decreased proliferation, reduced production of cytokines, and diminished release of the T-cell lineage. Besides, knockdown of Ubc12 in CD4+ T cells caused impaired T-cell receptor/CD28-induced proliferation because T cells were arrested in the G0/G1 phase of the cell cycle (113). Moreover, cytokine production like IL-2 and the differentiation of CD4+ T cells into effector Thcell subsets are decreased when the expression of Ubc12 is reduced.…”
Section: Neddylation and Hccmentioning
confidence: 99%